2004
DOI: 10.1111/j.1601-5223.2000.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

ITS Regions in Diploids of Aegilops (Poaceae) and their Phylogenetic Implications

Abstract: The nucleotide sequences of the internal transcribed spacer (ITS) of nuclear ribosomal DNA in nine diploid species representing six sections of Aegilops were determined by direct sequencing of PCR-amplified DNA fragments. These sequences were aligned with two ITS sequences of additional species from Genbank. Sequence divergences were estimated using Kimura two-parameter model, and the phylogenetic analyses were performed using the maximum parsimony (MP) and the neighbor-joining (NJ) methods with PAUP and PHYLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Kimber et al (1983) also found no preferential pairing between the two genomes. Wang et al (2000) claimed that the classification of section Comopyrum should be reconsidered based on their study of ITS sequences. Badaeva et al (1996a, b) also postulated that Ae.…”
Section: Phylogenetic Relationships Of Section Comopyrum-sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimber et al (1983) also found no preferential pairing between the two genomes. Wang et al (2000) claimed that the classification of section Comopyrum should be reconsidered based on their study of ITS sequences. Badaeva et al (1996a, b) also postulated that Ae.…”
Section: Phylogenetic Relationships Of Section Comopyrum-sectionmentioning
confidence: 99%
“…Later, many cytoplasmic and cytological studies (e.g., Tsunewaki et al, 1976;Teoh and Hutchinson, 1983) and an isozyme analysis (e.g., Benito et al, 1987) were done to reveal the genome relationships of Triticum-Aegilops species. More recent analyses have been focused on molecular markers in nuclei (Dvořák and Zhang, 1992;Sasanuma et al, 1996;Wang et al, 2000;Huang et al, 2002a, b;Sallares and Brown, 2004) or organelles (Tsunewaki and Ogihara, 1983;Terachi and Tsunewaki, 1986;Ogihara and Tsunewaki, 1988;Terachi and Tsunewaki, 1992). However, questions remain about the taxonomic relationships between Triticum-Aegilops sections and species.…”
mentioning
confidence: 99%
“…DNA barcoding is applied in many fields ( Pečnikar and Buzan, 2014 ), and allows animal, plant, and fungal species to be rapidly identified using one or several standard DNA sequences. Previous DNA barcoding studies of Aegilops species mainly sought to identify species that are difficult to distinguish morphologically ( Wang et al., 2000 ; Goryunova et al., 2005 ; Giraldo et al., 2016 ; Dizkirici et al., 2016 ), and phylogenetic analysis of Aegilops and Triticum species using DNA barcodes ( Yamane and Kawahara, 2005 ; Petersen et al., 2006 ; Meimberg et al., 2009 ). However, no studies have applied universal DNA barcodes to identify all species within the Aegilops genus.…”
Section: Introductionmentioning
confidence: 99%
“…many cytoplasmic and cytological studies (e.g., Tsunewaki et al, 1976;Teoh and Hutchinson, 1983) and an isozyme analysis (e.g., Benito et al, 1987) were done to reveal the genome relationships of Triticum-Aegilops species. More recent analyses have been focused on molecular markers in nuclei (Dvo ák and Zhang, 1992;Sasanuma et al, 1996Wang et al, 2000Huang et al, 2002a, b;Sallares and Brown, 2004) or organelles (Tsunewaki and Ogihara, 1983;Terachi and Tsunewaki, 1986;Ogihara and Tsunewaki, 1988;Terachi and Tsunewaki, 1992).…”
Section: Introductionmentioning
confidence: 99%